Remote control of industrial printer over internet - Hong, Jian Yang. (2008)
While Internet becomes popular, more and more traditional businesses become on line businesses, or E-business. Most of them are information services at the time being. Linking industrial equipment to internet is not so popular yet but the potential demand is there. Remotes operate a production line, on-line maintenance / service, on-line control, on-line monitor to industrial equipment, all these give a new way to operation a production line. A software is developed that links a factory equipment, Imaje JaimelOOO S4 ink jet printer, to internet / intranet so that the on-line network's workstations are able to access / control the factory equipment. The equipment provider can use it to provide on-line services. The equipment user can use this to monitor / control the equipment on-line too. This project is base on the study of V24 serial communication, winsocket communication, programming in Win32 , Imaje Jaime 1000 S4 ink jet printer V24 protocol, intranet and internet connection. This project involved MFC programming, V24 programming, winsocket programming, client/server programming and other techniques. After studying the related knowledge and techniques a test program has been developed and tested. The program includes two parts: client and server. Client is running locally to connect to the S4 printer. The server is running remotely and use to perform the remote controlling.